OFFENSIVE ARMAMENT OF THE KINGDOM OF VAN: METHODICAL AND MEDIA-TECHNOLOGICAL APPROACHES TO TRAINING (EDUCATION IN THE 21ST CENTURY, 2025)
The fundamental aim of history education lies in the acquisition of knowledge, the development of skills, and the cultivation of psychological dispositions and value orientations. Within the framework of 21st-century competences, UNICEF identifies soft skills, along with digital and professional competencies, as essential for all children and adolescents in order to expand their opportunities for lifelong learning, employability, and personal development.It is essential that the objectives of developing media literacy in the teaching of history are not introduced as a separate or supplementary component outside the school curriculum, but are instead embedded within the very logic and structure of the lesson itself.Therefore, we propose possible approaches to addressing these challenges within the framework of comparing Urartian and Assyrian offensive weaponry. Within the scope of our study, several lesson models were developed, aiming to integrate traditional and innovative methods. Particular attention was given to the incorporation of digital technologies into the teaching process, the application of the inquiry-based method, the use of electronic platforms, museum visits, and the strategy entitled ‘Historical Contradictory Interpretations.’The relevance of the research lies in the fact that, prior to this study, military history had not been incorporated into the teaching process through a combination of both traditional and innovative methods and strategies.The study led us to conclude that, for teaching the topic “A Comparative Analysis of the Offensive Weapons of the Kingdom of Van (Urartu) and Assyria”, a range of methods and strategies can be effectively employed, including ICT and inquiry-based learning, the implementation of new educational platforms, and museum-based lessons. The unifying element of these methods is the application of the inquiry-based approach. Our experimental results demonstrate that the integration of information technologies into the teaching process significantly enhances students’ motivation and engagement with the subject matter.
Keywords: History teaching methodology; digital and media technologies; learning objectives; Urartu; offensive weaponry